Penyusunan Anggaran Komprehensif Sebagai Alat Perencanaan Dan Pengendalian Laba Pada PT. X Di Sidoarjo - Putri Septiowati Rahayu; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna; Sutini Sutini; Heri Toni Hendro P (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This research was conducted at PT. X in Sidoarjo is a company engaged in the snack food industry. The purpose of conducting this research is to find out and analyze the preparation of the sales budget as a means of planning and controlling profits.The data used will be analyzed using qualitative methods, namely this research begins with data collection, observation and analysis of documents related to the object of research and ends with drawing conclusions. The data collection technique used is by interviewing and observing the company's activities.Based on the research conducted at the company, a problem was found, namely that it could be seen that the control carried out by PT. X related to the operational activity of selling snacks is not optimal, this is because the company does not yet have work standards or work targets which are manifested in the form of plans to prepare a sales budget and costs related to operational sales of the company's products.